Governor's Palace - (:unkn) unknown (Waterman, The Hatter, Clothier and Outfitter, Trinidad, 2009)
A picture of the Governor's residence, now known as the President's House, amidst the Botanical Gardens with its elongated façade of blue limestone, neo-Renaissance archways and Victorian detail. The postcard is addressed to Mr. John Potts, Swampscott, Mass., U.S.A. The postcard is dated February 6, 1921.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; 1921; Historic buildings--Trinidad and Tobago; President's House, The